2019
DOI: 10.1158/1541-7786.mcr-18-1147
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Uptake Is an Androgen-Enhanced Lipid Supply Pathway Associated with Prostate Cancer Disease Progression and Bone Metastasis

Abstract: De novo lipogenesis is a well-described androgen receptor (AR)-regulated metabolic pathway that supports prostate cancer tumor growth by providing fuel, membrane material, and steroid hormone precursor. In contrast, our current understanding of lipid supply from uptake of exogenous lipids and its regulation by AR is limited, and exogenous lipids may play a much more significant role in prostate cancer and disease progression than previously thought. By applying advanced automated quantitative fluorescence micr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 66 publications
(87 reference statements)
1
65
0
Order By: Relevance
“…Our previous longitudinal analysis of LNCaP tumor xenografts in a model of CRPC progression following castration showed that CRPC tumors contained significantly higher lipid levels than tumors resected from sham-castrated mice [33]. These lipids included essential fatty acid (FA) derivatives, indicating that development of CRPC is associated with enhanced uptake of exogenous, diet-derived lipids [16]. A detailed review of transcriptomic data from this study by gene set variation analysis (GSVA) revealed that castration caused a negative enrichment of pathways involved in lipogenesis, mitochondrial activity and oxidative phosphorylation in tumors at nadir of serum PSA levels compared to non-castrated tumor-bearing mice (intact, control).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous longitudinal analysis of LNCaP tumor xenografts in a model of CRPC progression following castration showed that CRPC tumors contained significantly higher lipid levels than tumors resected from sham-castrated mice [33]. These lipids included essential fatty acid (FA) derivatives, indicating that development of CRPC is associated with enhanced uptake of exogenous, diet-derived lipids [16]. A detailed review of transcriptomic data from this study by gene set variation analysis (GSVA) revealed that castration caused a negative enrichment of pathways involved in lipogenesis, mitochondrial activity and oxidative phosphorylation in tumors at nadir of serum PSA levels compared to non-castrated tumor-bearing mice (intact, control).…”
Section: Resultsmentioning
confidence: 99%
“…Above results suggested major changes to lipid metabolism networks by Enz. Previous studies, including our own work, have demonstrated that androgens strongly enhance cellular lipid content of PCa cells through enhanced lipogenesis [37, 38] and lipid uptake [16] and that AR antagonists block these lipid supply pathways. To measure Enz-induced changes to the cellular content of neutral lipids, lipid droplets, phospholipids and free cholesterol, we used quantitative single cell imaging (qSCI) of two fluorescent lipophilic dyes, Nile Red and Filipin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, prostate cancer has a unique dependency on lipid metabolism for energy production, which has been linked to enhanced fatty acid uptake [50], intracrine steroid synthesis and de novo fatty acid synthesis [49,50]. Despite the fact that the expression of many enzymes involved in synthesis, uptake and oxidation of lipids is under androgen control [51,52] and often upregulated in prostate cancer patients [53,54], blockade of androgen signaling will eventually cease to be e cacious in prostate cancer patients, suggesting that novel therapeutic agents that address directly lipid metabolism may represent a novel therapeutic opportunity [55]. The present data show that blockade of lipid metabolism inside prostate tumor cells using the AMPK inhibitor BAY-3827 has the potential to inhibit proliferation and future studies will show how this translates into the clinical setting.…”
Section: Discussionmentioning
confidence: 99%